ANALISIS STRATEGI BISNIS PADA WARUNG MAKAN CHINESE FOOD KENDEDESS DI KOTA KENDARI - Muhamad Bahtiar; Nursaban Rommy; Nurul Ittaqullah; Fauzan; Markoni (Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to identify the micro-business strategies of the Chinese Food Kendedess restaurant using SWOT analysis and to explore strategies for its development. The Kendedess restaurant implements various strategies to maintain the sustainability and quality of its culinary business. Its primary focus is on authentic flavors and friendly service, creating a comfortable atmosphere that encourages customer loyalty. During challenging economic times, the restaurant offers budget-friendly menus and discounts for online orders, allowing customers to enjoy high-quality meals without financial strain. Operational efficiency is maintained through clear task delegation among employees. The SWOT analysis reveals strengths such as a recognized brand (0.60), fresh cuisine (1.00), and excellent service (1.00), with a total strength score of 4.20. However, weaknesses like ineffective promotion (0.60) and suboptimal delivery service (0.50) pose challenges. Opportunities from lifestyle changes (1.00) and a large market segment (1.50) support growth, despite threats such as intense competition (0.90) and inflation (0.75). The total internal factor score is 6.65, while the total external factor score is 7.15, indicating challenges alongside opportunities for sustainable growth